Movement for the Defense of the Hungarian Nation. Statement in the United Nations during the 17th Session of the General Assembly - Héderváry, Claire de (1962)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): Movement for the Defense of the Hungarian Nation